INTEGRATED RISK BASED APPROACH ( INTEGRATED RISK BASED APPROACH (IRBA) DAN PERENCANAAN KEBERLANJUTAN TEMPAT PEMROSESAN AKHIR (TPA) GEDANGKARET KABUPATEN JOMBANG - Tuhu Agung Rachmanto; muhammad chumaidy maimun abdillah ainani jundah (EnviroUS, 2021)
Nowadays, the Gedangkaret landfill in Jombang, has one of the supporting facilities are not managed properly, such as ditches and pools channel leachate was buried with much of garbage, clogged, and it is no longer maintained. The leachate pool behind the landfill was only functions to accommodate leachate without any further management processes. Both systems use a barrier layer of leachate, leachate channels, and soil as a cover of a pile of garbage, and at each end of the operation of garbage covered with soil to minimize impacts on public health. In planning the rehabilitation of the Gedangkaret landfill in Jombang this time, held evaluating the feasibility of the landfill with Integrated Risk Based Approach method (IRBA), which refers to the regulation of the Minister of Public Works and Public Housing (PUPR) of the Republic of Indonesia Number 3 in 2013 annex V. With a land area of 8.7 hectares, the Gedangkaret landfill is currently still being operated using the controlled landfill method, where the filling is carried out when the cells are full or the land used for filling is available. Some parts of the landfill also have been filled by using overburden. Gas management is carried out by flaring the landfill’s methane gas. Landfill leachate management is done by using stabilization ponds. The result of quantitative analysis using the risk index assessment method shows that the risk index value of the Gedangkaret Landfill in the overall aspects is 538.48. Broadly speaking, the rehabilitation activities carried out from the results of the risk index assessment are in the form of groundwater contamination (planning of basement system and stockpile zone cover to minimize the potential for leachate to infiltrate into the ground), future use (planning of new stockpiling zones and temporary stockpile zones), existing landfills (slope stabilization of the dumping zone and planning of the embankment zone), air pollution (planning for gas management and landfill buffer zones), leachate production (planning for leachate pipeline construction and management using leachate treatment plant).